Study on effects of the train-induced airflow on the temperature field of single-track high-speed railway tunnels in cold regions - Jun Zhou; Liyuan Wu; Yan Gao; Xu Chen; Rongrong Liu (Scientific Reports)
Abstract High-speed trains bring cold air into tunnels, significantly affecting the temperature field in cold-region tunnels, leading to risks of lining freeze-thaw damage, track deformation, and safety hazards, which is detrimental to thermal insulation design. Using the Kunlunshan Tunnel as a case study and based on unsteady flow theory, this study constructed the Navier-Stokes equations and proposed a theoretical calculation method for train-induced airflow. Dynamic mesh technology was adopted to develop an “equivalent wind speed” train-induced-airflow-temperature coupling computational model. The main idea of this model is to divide the effect of external wind speed on the tunnel into three distinct phases: the train-induced airflow phase, the residual airflow phase, and the natural wind phase. During each phase, the changes in wind speed are governed by the principle of conservation of cold air volume and converted into a steady airflow equivalent for that specific phase. This model was used to investigate the effects of train frequency, ground temperature of surrounding rock, external temperature, and external wind speed on the temperature field variation in single-track high-speed railway tunnels in cold regions. After verification, the temperature field inside the tunnel calculated by the “equivalent wind speed” method was in good agreement with the measured data, and can be used for subsequent numerical simulation calculations. The results show that when the interval between two trains is less than 20 min, the average temperature in the tunnel decreases by approximately 1.71 ℃ due to the significant impact of train-induced airflow. The impact of the ground temperature of surrounding rock on the longitudinal temperature gradient in cold-region tunnels ranges from 0.059 ℃ to 1.13 ℃ for every 100 m, and the ranges for external temperature and external wind speed are 0.080 ℃ to 2.286 ℃ and 0.002 ℃ to 1.134 ℃, respectively.